Psychological Features of Infertility - Kemas Muhammad Afif Rahman (Scientia Psychiatrica, 2021)
Infertility is defined as the inability to produce, or give birth to a baby naturally. Generally, specialists define infertility as not being able to get pregnant after trying for at least one year. The relationship between infertility and psychology is very complicated. On the one hand, infertile couples are more likely to experience stress and have a greater risk of experiencing psychological disorders compared to normal and healthy couples. On the other hand, high levels of psychological distress are indicated to increase infertility. Therefore, in this review, the main factors that can lead to increased stress in couples trying to conceive, psychological stress as a cause of infertility, on female and male fertility, including stress and depression.